2013
DOI: 10.2139/ssrn.2292277
|View full text |Cite
|
Sign up to set email alerts
|

Political Dynasties and Poverty: Resolving the 'Chicken or the Egg' Question

Ronald U. Mendoza,
Edsel L. Beja,
Victor Soriano Venida
et al.

Abstract: Abstract"Political dynasty" refers to the situation wherein members of the same family are occupying elected positions either in sequence for the same position, or simultaneously across different positions. In the Philippines, political dynasties are prevalent in areas with more severe poverty.Two explanations for this situation have been proposed: poverty brings about political dynasties, or political dynasties engender poverty. These arguments suggest that the relationship between political dynasties and pov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…In this case, whether the granting of authority in finances can be utilized properly, where decision-making will have a consequence in this case will be seen how budget allocations in the region led by the political dynasty whether the decision is taken prioritize social interest or family interest, so the budget allocated will be right on target and able to improve people's welfare. Previous research has shown that poor political dynasties in dealing with poverty thereby creating poverty or undesirable performance (Bardhan, 2005, Nuritomo, 2014Sujarwoto, 2015;Kautsar, 2015), but others assume that dynasties do not create poverty but dynasty is synonymous with poverty (Mendoza, 2013(Mendoza, , 2014(Mendoza, , 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, whether the granting of authority in finances can be utilized properly, where decision-making will have a consequence in this case will be seen how budget allocations in the region led by the political dynasty whether the decision is taken prioritize social interest or family interest, so the budget allocated will be right on target and able to improve people's welfare. Previous research has shown that poor political dynasties in dealing with poverty thereby creating poverty or undesirable performance (Bardhan, 2005, Nuritomo, 2014Sujarwoto, 2015;Kautsar, 2015), but others assume that dynasties do not create poverty but dynasty is synonymous with poverty (Mendoza, 2013(Mendoza, , 2014(Mendoza, , 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Besley and Querol (2013) assume that society will accept dynastic leadership when its economic performance is good. Mendoza et al (2013Mendoza et al ( : 20142016) found that political dynasties do not affect poverty levels, but the poverty would strengthen the political dynasty. In addition, the decrease in poverty and inequality in income distribution is a direct and indirect impact of fiscal decentralization policies in which local governments play an important role through open and direct policies (Sepulveda and Vazques, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…They are sometimes aligned with the rich group and sometimes with marginalized people and there is always the possibility for uncertainty to the form of political alliance and power (14). The dynasty politics creates a deep root power structure and it is very difficult to manage and creates instability (15). Moreover, there are some unethical practice in elections and there is no fairness and there is always a possibility for instability and large number of people get confused and divided (16).…”
Section: Situation Of Low-and Middle-income Countries and Healthmentioning
confidence: 99%
“…Pendapat ini bisa ditelusuri melalui program-program petahana mendekati pilkada diarahkan kepada pembangunan infrastruktur dan hibah bansos. Studi yang dilakukan Mendoza dkk di Filipina bahwa politik kekerabatan menyebabkan kemiskinan (Mendoza et al, 2013). Tidak hanya studi yang dilakukan oleh Querubin menilai bahwa dinasti politik sangat memungkinkan terjadinya penyelewengan kekuasaan dan etika politik sehingga membuat pemerintahan tidak berjalan dengan efektif dan efisien serta menciptakan ketidakadilan (Querubin, 2016).…”
Section: Pendahuluanunclassified